The hurt(ful) body performing and beholding pain, 1600-1800 - Macsotay Bunt, Tomas; Haven, Cornelis van der 1978-; Vanhaesebrouck, Karel 1978- (Manchester University Press, 2017)
This book offers a cross-disciplinary approach to pain and suffering in the early modern period, based on research in the fields of literary studies, art history, theatre studies, cultural history and the study of emotions. The volume's two-fold approach to the hurt body, defining 'hurt' from the perspectives of both victim and beholder - as well as their combined creation of a gaze - is unique. It establishes a double perspective about the riddle of 'cruel' viewing by tracking the shifting cultural meanings of victims' bodies, and confronting them to the values of audiences, religious and popular institutional settings and practices of punishment. It encompasses both the victim's presence as an image or performed event of pain and the conundrum of the look - the transmitted 'pain' experienced by the watching audience
Daten, Ort und Name der Konferenz im Internet ermittelt
Keywords: Verletzung -- Motiv; Schmerz -- Motiv; Gewalt -- Motiv; Körper -- Motiv; Kunst; Konferenzschrift -- Royal Flemish Academy of Belgium for Science and the Arts -- 21.11.2013-22.11.2013 -- Brüssel